Developing an Interactive Digital Handout for Momentum and Impulse Material Physics in High Schools - Pahlawan, Ridho; ., Ismet; ., Syarifuddin (Universitas Pendidikan Ganesha, 2021)
Understanding physics lessons is generally caused by the lack of innovative teaching materials that facilitate learning. This study aims to develop interactive digital material on momentum and impulse physics in high schools. This research is development research using the Allesi and Trollip development model. This research and development procedure goes through 3 stages, namely planning, design, and development. The techniques used to collect data were observation, interviews, and tests. The instrument used in collecting data was a questionnaire. The subjects of this study were tenth-grade senior high school students. The techniques used to analyze the data are qualitative and quantitative analysis. The study results were the average learning outcome before being given an interactive digital handout display of the momentum and impulses of physics material was 48.93. Then the educators taught using interactive digital physics handouts using the articulate storyline application to increase the average score of students’ cognitive learning outcomes to 81.27. The increase in the average score of students was measured using the N-gain score, and the result was 0.70 in the moderate category. It can be concluded that e-learning tools have been tested effectively to improve student learning outcomes. This research implies that the developed e-learning tools can be used to help students in learning.